Efficacy and Safety of Trigeminal Nerve Stimulation for Migraine: A Meta-Analysis of Randomized Controlled Studies - Deng, Chunyan; Li, Yongmei (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2023)
Objective Trigeminal nerve stimulation may have some potential in treating migraine, and this meta-analysis aims to study the efficacy and safety of trigeminal nerve stimulation for migraine patients.Methods We have searched several databases including PubMed, EMbase, Web of science, EBSCO and Cochrane library databases, and selected the randomized controlled trials (RCTs) comparing the efficacy of trigeminal nerve stimulation for migraine patients. This meta-analysis was conducted using the random-effect or fixed-effect model based on the heterogeneity.Results Four RCTs were included in this meta-analysis. Compared with sham procedure in migraine patients, trigeminal neurostimulation benefited to improve pain freedom at 2 h (OR=2.69; 95% CI=1.30 to 5.56; P=0.007), pain relief at 2 h (OR=2.05; 95% CI=1.53 to 2.74; P<0.00001), pain freedom at 24 h (OR=2.00; 95% CI=1.42 to 2.81; P<0.0001) as well as pain relief at 24 h (OR=1.71; 95% CI=1.25 to 2.33; P=0.0007), and reduce rescue medication (OR=0.70; 95% CI=0.52 to 0.95; P=0.02), but demonstrated no obvious impact on the incidence of adverse events (OR=2.24; 95% CI=1.21 to 4.13; P=0.01).Conclusions Trigeminal nerve stimulation is effective and safe for the treatment of migraine patients.
Keywords: headache; pain; physical therapies